Inscripciones y estudios epigráficos de los países de lengua alemana - Koch, Walter (Estudios humanísticos. Geografía, historia y arte, 1996)
This article is based on medieval inscriptions in Central Europe and its graphic evolution from the early Middle Ages up to the dawn of the Modern Age.